Melting line of polymeric nitrogen - Yakub, L.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We made an attempt to predict location of the melting line of polymeric nitrogen using two equations for Helmholtz free energy: proposed earlier for cubic gauche-structure and developed recently for liquid polymer-ized nitrogen. The P–T relation, orthobaric densities and latent heat of melting were determined using a standard double tangent construction. The estimated melting temperature decreases with increasing pressure, alike the temperature of molecular–nonmolecular transition in solid. We discuss the possibility of a triple point (solid–molecular fluid–polymeric fluid) at 80 GPa and observed maximum of melting temperature of nitrogen.